The Application of Game Mechanics and Technological Trend in Game-Based Learning: A Review of the Research - Mhd. Adhitiya Okta Riyandi; Harry Budi Santoso; Panca Oktavia Hadi Putra (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2023)
The rapid development of information technology affects numerous aspects of human life, including education. An example of an IT application in education is game-based learning. Game-based learning has been implemented in various fields or subjects on various platforms. This is due to the potential of game-based learning to enhance student engagement in the learning process. However, the effectiveness of this method needs to be further studied. This systematic review of the literature aimed to explore the mechanics of games that are applied in current research on game-based learning, accompanied by the trend of technological use in research papers published in this domain. This study covered 30 journal and conference proceedings papers published from 2012-2022. The review was conducted using the Kitchenham method. The selected articles were then analyzed to determine the engagement model used in each paper (Feedback Model, Incentive and achievement model, and Progression Model). Findings included the trend of research in this field (technology applied to each research, on-line feature, study majors/subject) are displayed based on the time paper were published. The study result indicated that all previous research used at least one of the engagement models, with 12 articles using the three models. In terms of technology, it was found that the adoption of web-based technology has been increasing in recent years, including online features that have also increased, along with the study subjects who implemented game-based learning. In summary, game-based learning can be applied in a wide range of subjects and platforms with the support of its characteristic, making learning more flexible.